What Are Constructions, and What Else Is Out There? An Associationist Perspective - Kapatsinski, Vsevolod (Frontiers in Communication, 2021)
Constructionist approaches to language propose that the language system is a network of constructions, defined as bidirectional mappings between a complex form and a meaning. This paper critically evaluates the evidence for and against two possible construals of this proposal as a psycholinguistic theory: that direct, bidirectional form-meaning associations play a central role in language comprehension and production, and the stronger claim that they are the only type of association at play. Bidirectional form-meaning associations are argued to be plausible, despite some apparent evidence against bidirectionality. However, form-meaning associations are insufficient to account for some morphological patterns. In particular, there is convincing evidence for productive paradigmatic mappings that are phonologically arbitrary, which cannot be captured by form-meaning mappings alone, without associations between paradigmatically related forms or constructions. Paradigmatic associations are argued to be unidirectional. In addition, subtraction and backformation at first glance require augmenting the associative networks with conditioned operations (rules). However, it is argued that allowing for negative form-meaning associations accommodates subtraction and backformation within the constructionist approach without introducing any additional mechanisms. The interplay of positive and negative form-meaning associations and paradigmatic mappings is exemplified using a previously undescribed morphological construction in Russian, the bez-Adjective construction.